Forensics Meets Ecology – Environmental DNA Offers New Capabilities for Marine Ecosystem and Fisheries Research - Schadewell, Yvonne; Adams, Clare I. M. (Frontiers in Marine Science, 2021)
Climatic changes and anthropogenic pressures affect biodiversity and community composition. These biodiversity shifts are recognized in marine ecosystems, but the underlying processes are barely understood so far. Importantly, human well-being highly relies on oceanic services, which are affected by anthropogenic pressures. Here, we review how interdisciplinary research approaches, with the incorporation of eDNA (environmental DNA) analyses, can help increase the understanding of complex ecosystem processes and dynamics, and how they affect ecosystem services. We discuss marine conservation issues in the light of life cycle aspects and conclude that eDNA can improve our ecological knowledge in some instances, for example, in tracking migration patterns. We also illustrate and discuss the application of eDNA analysis within the context of population genetics, epigenetics, geochemistry and oceanography. Embedded into an interdisciplinary context, eDNA can be exploited by a huge variety of methodological techniques, and can resolve spatio-temporal patterns of diversity, species, or even populations within ecological, evolutionary, and management frameworks.